2015
DOI: 10.1002/tal.1229
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced performance through a dual isolation seismic protection system

Abstract: While base isolation successfully decreases the accelerations transmitted to a structure, a tradeoff is large unfavorable displacements in the isolation layer. This study investigates an innovative system, termed 'dual isolation', which applies two layers of isolation at the base and at mid-story to resolve this issue. A linear analytical solution for the equation of motion of the proposed system is developed on the basis of linear isolation theory. This creates a foundation to assess the behavior of various t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Shaikhzadeh and Karamoddin [7] reported that in a strong near-fault earthquake, polynomial friction pendulum isolator and variable curvature friction pendulum system or conical friction pendulum isolator and variable frequency pendulum isolator could respectively be chosen based on whether reduction of base displacement or superstructure acceleration is the main concern of the structural designer. The undeniable need to control excessively large unfavorable displacements across the isolation layer was highlighted by Becker and Ezazi [8] while confirming that base isolation was indeed successful in decreasing the accelerations transmitted to a structure. Mazza [9] studied the seismic demand of base-isolated irregular structures subjected to pulse-type earthquakes.…”
mentioning
confidence: 86%
“…Shaikhzadeh and Karamoddin [7] reported that in a strong near-fault earthquake, polynomial friction pendulum isolator and variable curvature friction pendulum system or conical friction pendulum isolator and variable frequency pendulum isolator could respectively be chosen based on whether reduction of base displacement or superstructure acceleration is the main concern of the structural designer. The undeniable need to control excessively large unfavorable displacements across the isolation layer was highlighted by Becker and Ezazi [8] while confirming that base isolation was indeed successful in decreasing the accelerations transmitted to a structure. Mazza [9] studied the seismic demand of base-isolated irregular structures subjected to pulse-type earthquakes.…”
mentioning
confidence: 86%
“…The equations summarized in Table are influenced by the type of excitation force . Various authors have reported the use of PMI using actual earthquake records, but limited studies are reported on optimizing this system. In addition, the results obtained from different analyses are subject to uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…The five models are the multiple isolation and building connection model (proposed model), the base-isolated and building connection model, the building connection model without isolation, the multiple isolation model without building connection (Pan et al, 1995;Becker andEzazi, 2016, Fujita et al, 2016), and the base-isolated model without building connection. Table 1 shows the first to third natural periods of various building models to be considered here and the first to third damping ratios of those models.…”
Section: Hybrid Control System Using Multiple Isolation and Building mentioning
confidence: 99%
“…In this paper, a new hybrid passive control building system is proposed in which a multiple isolation building model (Pan et al, 1995;Becker andEzazi, 2016, Fujita et al, 2016) is connected to another non-isolated building (free wall) with oil dampers. A similar type of connected buildings without isolation and another type of base-isolated buildings with connection have been designed and constructed by Obayashi Corporation and Shimizu Corporation in Japan as an apartment house with a car parking tower (Murase et al, 2013;Kasagi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%